Sesame Yield Response to Deficit Irrigation and Water Application Techniques in Irrigated Agriculture, Ethiopia - E. K. Hailu; Y. D. Urga; N. A. Sori; F. R. Borona; K. N. Tufa (International Journal of Agronomy)
The study was conducted at Werer Agricultural Research Center, Addis Ababa, for two years, 2013 and 2015, during main seasons and for three years, 2012/13, 2013/14, and 2014/15, during the cool period cropping season (November to February) as in the local cropping calendar. The study was aimed at identifying optimum soil moisture stress for sesame and thereby determining appropriate water-saving irrigation methods and also productivity under limited water resource conditions. Nine treatments with three levels of irrigation water percentage based on evapotranspiration of the crop (ETc) (100% ETc, 75% ETc, and 50% ETc) and three types of furrow irrigation methods (alternate furrow, fixed furrow, and conventional furrow) were used. The study design was randomized complete block design (RCBD) with three replications. The yield of sesame had significant (p<0.05) variation among treatments due to deficit irrigation levels and application methods for sesame planted in main seasons. The highest mean yield of 937.50 kg/ha and 2797.6 kg/ha was obtained from the treatment of 50% ETc with alternate and conventional furrow application methods in 2013 and 2015, respectively. The combined mean yield of two years (2013–2015) showed different levels of deficit irrigation, and irrigation methods had a significant effect (p<0.05) on main season planted sesame. Hence, the highest mean yield of 1846.7 kg/ha was obtained from the application of 50% ETc with the conventional furrow application method. In the cool planting season, the highest mean yield of 528.55 kg/ha, 1432.3 kg/ha, and 1562.5 kg/ha was obtained from treatments of 50% ETc, 75% ETc, and 100% ETc with the conventional furrow application method in 2012/13, 2013/14, and 2014/15, respectively. Moreover, during the same period over years, combined analysis showed that the highest mean yield of 1053 kg/ha was obtained from application of 100% ETc with the conventional furrow application method. Thus, it is concluded that a deficit irrigation treatment of 50% ETc with the conventional furrow application method for main season and application of 100% ETc with the conventional furrow application method for cool planting season are best practices of water-saving strategies for irrigated agriculture system.